Impact of urea-based diets on production of Red Chittagong Cattle (Bangladesh Veterinarian, 2010)
The production traits of Red Chittagong Cattle (RCC) were studied using two diets: A [Urea-molasses-rice straw (UMRS), Green Grass and Concentrate] and B [Rice straw, Green Grass and Concentrate]. In cows fed diets A and B, birth weights of calves were 15.2 and 14.1 kg (P0.05), lactation length 254.8 and 247.1 days (P>0.05), age at first oestrus 28.4 and 25.6 months (P